World Health Organization-World Federation of Societies of Anaesthesiologists (WHO-WFSA) International Standards for a Safe Practice of Anesthesia. (June 2018) - Gelb, Adrian W.; Morriss, Wayne W.; Johnson, Walter; Merry, Alan F.; Abayadeera, Anuja; Belîi, Natalia; Brull, Sorin J.; Chibana, Aline; Evans, Faye; Goddia, Cyril; Haylock-Loor, Carolina; Khan, Fauzia; et al.
Abstract : The International Standards for a Safe Practice of Anesthesia were developed on behalf of the World Federation of Societies of Anaesthesiologists (WFSA), a nonprofit organization representing anesthesiologists in 150 countries, and the World Health Organization (WHO). The recommendations have been approved by WHO and the membership of WFSA. These Standards are applicable to all anesthesia providers throughout the world. They are intended to provide guidance and assistance to anesthesia providers, their professional organizations, hospital and facility administrators, and governments for maintaining and improving the quality and safety of anesthesia care. The Standards cover professional aspects; facilities and equipment; medications and intravenous fluids; monitoring; and the conduct of anesthesia.HIGHLY RECOMMENDED standards, the functional equivalent of mandatory standards, include (amongst other things): the continuous presence of a trained and vigilant anesthesia provider; continuous monitoring of tissue oxygenation and perfusion by clinical observation and a pulse oximeter; intermittent monitoring of blood pressure; confirmation of correct placement of an endotracheal tube (if used) by auscultation and carbon dioxide detection; the use of the WHO Safe Surgery Checklist; and a system for transfer of care at the end of an anesthetic. The International Standards represent minimum standards and the goal should always be to practice to the highest possible standards, preferably exceeding the standards outlined in this document.